A Development of Learning Media in Fluids in Higher Education Based on Android - Negara, Teguh Puja (IJNMT (International Journal of New Media Technology), 2023)
The impact of the corona virus pandemic has disrupted all activities in Indonesia, especially in teaching and learning activities in universities. The lecture process has changed, such as the ban on face-to-face meetings, which has an impact on the learning system on campus. Therefore, the government has implemented an online learning system to overcome the massive spread of the virus while maintaining lectures. One of the issues at issue is practicum activities which require students to come directly to the laboratory, so a solution is needed, namely learning media that can support distance learning to remain effective. The learning media in this study used the Multimedia Development Life Cycle (MDLC) method using Frame by Frame, Low-poly modeling and Shader Graph techniques. The results of this study are an Android-based fluid case learning medium, where, in the application, users can try simulations in the form of 3D animations and work on practice questions and post-tests. Thus, users can better understand fluid materials without the need to do practical work in a physics laboratory.